Seven Reasons-why China is not a Threat to U.S Hegemony? - Tomja, Alida (Acta Universitatis Danubius. Relationes Internationales, 2023)
Abstract Many researchers see China as the most likely competitor to balance US power, even to overtake it as an indisputable global power. Some of them, according to the theory of transition, have predicted that the United States and China are the two main powers forced to engage in the biggest conflicts of the future. Even recent polls show that most people share the view that China will replace the United States as the world's leading superpower. In this regard, China has become the most quoted nation when it comes to any possible change of the unipolar system structure to a two or multipolar one. The purpose of this study is to analyze whether China has enough capacity to become hegemonic power by challenging the role of the United States. This study provides a tableau of important factors besides those of an economic and military nature that limit the potential of this state to be a global superpower thus challenging American hegemony. Through literature, documentation review and secondary quantitative data produced by other research materials, this study concludes that China continues to be an Asian-continental power without the capacity to project its power across the globe as the United States. Keywords: United States, China, International System, Challenge